The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3319/tao.2005.16.4.909(gig)
|View full text |Cite
|
Sign up to set email alerts
|

Tritium Concentrations and Radiocarbon Ages of Gushing Groundwater from Hsuehshan Tunnel, Northern Taiwan

Abstract: ABSTRACT1 Department of Geosciences, National Taiwan University, Taipei, Taiwan, ROC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…28 transverse walking tunnels, eight vehicle tunnels, and shafts and air vents (including three ventilation stations, three ventilation repeaters, 12 transverse ventilation tunnels, and six airshafts) comprise the exhaust system of the two main tunnels. The Hsuehshan Tunnel boasts the largest group of dual-bore highway tunnels in the World, and its construction cost 640 million USD [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…28 transverse walking tunnels, eight vehicle tunnels, and shafts and air vents (including three ventilation stations, three ventilation repeaters, 12 transverse ventilation tunnels, and six airshafts) comprise the exhaust system of the two main tunnels. The Hsuehshan Tunnel boasts the largest group of dual-bore highway tunnels in the World, and its construction cost 640 million USD [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hsueshan Tunnel construction at the catchment lasted for over 16 years (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) of artesian water, which was proven to have existed for 8000 years (Liu et al, 2005), indicated that it contained underground reservoirs. Certain amounts of tunnel drilling debris as well as a large quantity of groundwater were exported into the downstream reservoir.…”
Section: Site Descriptionmentioning
confidence: 98%
“…In addition, such gas-charged sediments in the seafloor and their bubbling plumes present a high risk to offshore construction. Liu et al (2005), investigating gushing water during the Hsuehshan Tunnel construction in northern Taiwan, measure carbon and tritium isotopic compositions and recognize two different recharge sources for the gushing groundwater. Such isotopic compositions reflect local hydrogeological characteristics of the rock formations along the tunnel and are helpful in assessing excavation methods.…”
mentioning
confidence: 99%